A10.14 Identification of Novel ACPA Targets in Rheumatoid Arthritis Synovial Tissues Using 2D Gel Electrophoresis and Mass Spectrometry. (25th February 2013) - Ossipova, E; Oliynyk, G; Cerqueira, C; Becker, S; Ytterberg, J; Auer, G; Klareskog, L; Jakobsson, P-J
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterised by synovial joint inflammation and pannus formation that leads to degradation of cartilage and the underlying bone. Presence of anti-citrullinated protein/peptide antibodies (ACPA) in 60–70% of patients with RA is one of the major characteristics of the disease and associates with a more aggressive disease course, suggesting a direct pathogenic involvement of ACPA in disease initiation and progression. ACPA recognises several citrullinated proteins like fibrinogen, α-enolase, vimentin, and collagen II. In this study, we aim for the identification of novel ACPA targets in synovial tissues of patients with RA. Materials and Methods: RA synovial tissues were obtained from patients undergoing joint replacement surgery for rheumatoid arthritis of the knee or elbow at the Karolinska University Hospital, Stockholm, Sweden. Synovial tissues were frozen in liquid nitrogen shortly after resection and stored at –80°C. All procedures were approved by Northern Stockholm Ethical Review Board and tissues were obtained with informed patient consent. Proteins, extracted from pulverised frozen synovial tissues and solubilised in lysis buffer, were resolved in 2D PAGE. Separated proteins were directly transferred to a nitrocellulose membrane and probed with human ACPA pool obtained using CCP2 affinity columns, kindly provided by Euro-Diagnostica, as described previously. [1] Human IgG and CCP2 flow-through fraction were used as control antibodies. Silver stained gel spots, corresponding to WB signals, were extracted from 2D gels, in-gel digested using Lys-C, and resulting peptides were identified using mass spectrometry. Results: By combining 2D gel electrophoresis with mass spectrometry, we have identified several novel potential ACPA targets as well as already characterised proteins. It remains to demonstrate if these proteins are citrullinated. Conclusions: Here we demonstrate an extensive ACPA reactivity against novel proteins in RA synovial membranes. The results encourage further exploration of the role of these proteins/peptides in rheumatoid arthritis both as additional biomarkers as well as their potential roles in the pathogenesis of RA. Reference: Ossipova E, Cerqueira C, Reed E, et al, Affinity purification and characterization of anti-citrullinated protein/peptide antibodies from plasma and synovial fluids of patients with rheumatoid arthritis (submitted).